Optical complex for the study of pulsating aurora with sub-millisecond time resolution on the basis of the Verkhnetulomsky observatory. (1st September 2022) - Belov, A.A.; Klimov, P.A.; Kozelov, B.V.; Barrillon, P.; Blin-Bondil, S.; Marszał, W.; Murashov, A.S.; Parizot, E.; Prévôt, G.; Roldugin, A.V.; Sharakin, S.A.; Szabelski, J.; et al.
Abstract: A new telescope-spectrometer was installed at Verkhnetulomsky observatory (68 ∘ 36'N, 31 ∘ 47'E) to supplement the data from all-sky cameras with measurements of the fine space–time structure of the auroral luminescence. The telescope uses 5 cm ultraviolet (UV) transparent lens as an optical system and a matrix of multi-anode photomultiplier tubes as a photo detector. The angular resolution of the telescope is 1.2 ∘ and the temporal resolution is 0.3 ms. The telescope observes a central part (20 ∘ ) of the all-sky camera field of view (FOV). Description of both optical instruments and results of the first joint measurements are presented. Graphical abstract: Highlights: A new instrumental complex for pulsating aurora studies was developed and put into operation. This complex allows to measure fine space-time structures of aurora emission. First overnight data of observations are analyzed and presented.